علاج الهالات السوداء بأحماض الفواكه وفيتامين ك - تاج حماد, فخر (Latakia University Journal -Medical Sciences Series, 2014)
تسبب الهالات السوداء حول العين مشكلة جمالية ونفسية، وهي ثاني مشكلة تجميلية كبيرة من حيث الشيوع في العالم بعد التجاعيد، فكان لا بد من البحث عن خيارات علاجية جديدة تحسن من الحالات غير المقبولة تجميلياً. في بحثنا هذا ندرس فعالية كل من أحماض الفواكه وفيتامين ك في علاج الهالات السوداء حول العين عند 120 مريضاً تم تقسيمهم بشكل عشوائي على ثلاث مجموعات كل منها تضم 40 مريضاً، في المجموعة الأولى تم استخدام أحماض الفواكه بتركيز 40% كعلاج وحيد، وفي المجموعة الثانية استخدم فيتامين ك بشكل موضعي بتركيز 2% كعلاج وحيد أما في المجموعة الثالثة استخدم مركب معالجة من أحماض الفواكه وفيتامين ك، وذلك لتحديد أفضل البروتوكولات العلاجية لعلاج الهالات السوداء حول العين. Dark circles around the eyes cause cosmetic and psychological problems. They are the most common cause of major cosmetic problems after wrinkles. Thus there is a need to look for new therapeutic options to improve the unacceptable cosmetic cases. In our research, we evaluated the effectiveness of each fruit acid and vitamin k in the treatment of dark circles around the eyes in 120 patients. The patients were randomly divided into three groups of 40 patients each. In the first group, fruit acid of 40% density was used as the only treatment. In the second group, topical vitamin k of 2% density was used as the only treatment. In the third group, both of fruit acids and the vitamin k were used for treatment. The goal of this study was to determine the best therapeutic protocol to treat dark circles around the eyes.